Gene Editing in Dairy Cows: Advancing Milk Yield, Health, and Resilience for Sustainable Dairy Development - Md. Emran Hossain; Shilpi Islam (International Journal of Genetic Modifications and Recombinations, 2025)
Gene editing has emerged as a transformative tool in dairy science, offering unprecedented opportunities to enhance productivity, improve animal health, and bolster resilience against environmental challenges. This study explores the potential of gene editing technologies, including CRISPR-Cas9, in advancing milk yield, optimizing milk composition, and addressing genetic disorders in dairy cows. Specific applications include targeting genes associated with mastitis resistance, improving feed efficiency, and introducing heat tolerance traits to adapt to climate variability. Additionally, gene editing provides solutions to reduce greenhouse gas emissions by modifying rumen microbiota, contributing to environmentally sustainable dairy farming practices. Ethical considerations and regulatory frameworks are also highlighted, addressing public concerns about animal welfare and food safety. This paper emphasizes the integration of gene editing into breeding programs to ensure precise, heritable trait modifications while minimizing off-target effects. By focusing on these advancements, gene editing can revolutionize dairy farming, enabling sustainable dairy development that balances productivity, animal well-being, and environmental stewardship. However, challenges such as societal acceptance, cost-effectiveness, and long-term impacts warrant further investigation. The findings underscore the critical role of gene editing in shaping the future of dairy production systems, offering a pathway toward sustainable and efficient dairy farming practices.
Keywords: CRISPR-Cas9; Environmental sustainability; Gene Editing; dairy cattle; disease resistance; feed efficiency; genetic improvement; milk yield; resilience